Upaya Meningkatkan Kemampuan Berbahasa Melaluikegiatan Bermain Peran Pada Anak Di TK Desa Ngadipiro Kecamatan Nguntoronadi Kabupaten Wonogiri Tahun Ajaran 2015/2016 - SARI, Ayu Sekar, Dra. Surtikanti, S.H.,M.Pd, WILI ASTUTI, S.Pd., M.Pd (2016)
The purpose of the research is to increase children languag eability by employing role play method at TK Desa Ngadipiro 2015/2016. The subjects of the research are thirteen children of TK Desa Ngadipiro. This research is a class research. This research employs Kurt Levin methods. The methods collected data by observasi, interviews, and condition of the class. Techniques used to check the validity of the data is the data triangulation. This research shows that the level of language skills of children in TK Desa Ngadipiro 2015/2016 before being implemented action research level language skills of children of only 41.63%. The research is the first cycle to 54.57%, the second cycle increased to 69.71%, and the third cycle increased to 83.39%. percentage increase from prasiklus (first conditions) to the first cycle was 12.94%, the increase from the first cycle to the second cycle was 15.14% and an increase from the second cycle to the third cycle was 13.68%. The results of the study meets the indicators of achievement. Basedon the role play method is able to increase to language the ability of ECE at TK Desa Ngadipiro. Keyword : early child language ability, role play method